Speech and the Truth-Seeking Value - Murchison, Brian C. (The Columbia Journal of Law & the Arts, 2015)
Courts in First Amendment cases long have invoked the truth-seeking value of speech, but they rarely probe its meaning or significance, and some ignore it altogether. As new cases implicate questions of truth and falsity, thorough assessment of the value is needed. This Article fills the gap by making three claims. First, interest in truth-seeking has resurfaced in journalism, politics, philosophy, and fiction, converging on a concept of provisional or “functional” truth. Second, the appeal of functional truth for the law may be that it clarifies thinking about a range of human priorities—survival, progress, and character—without insisting on truth in an absolute or transcendent sense. Third, the law’s current treatment of truth-seeking in First Amendment cases turns on whether a case implicates the truth of the past, present, or future. Cases about past truth involve its knowability; cases about present truth involve its hiddenness; and cases about future truth involve its falsification. Because judicial treatment of truth-seeking in each of these groupings is underdeveloped, legal thought can benefit from literary works by three major novelists: Paul Scott, author of Staying On; Kazuo Ishiguro, author of Never Let Me Go; and Ian McEwan, author of Atonement. Each of these works clarifies an important aspect of the truth-seeking value of expressive freedoms. The Article concludes by considering the value’s limitations, focusing on the complex setting of campaign finance.